Endoplasmic reticulum stress orchestrates tumor metabolism and immunity: new insights into immunometabolic therapeutics - Fu, Zhang; Li, Mengyue; Zhou, Huaixiang; Zhong, Xin; Zhang, Zhiqiang; Meng, Xianwen; Jiang, Youheng; Wang, Tao; Li, Ningning (Frontiers in Immunology, 2025)
Endoplasmic reticulum (ER) stress and its adaptive signaling network have emerged as central regulators of tumor progression, metabolic rewiring, and immune modulation. Within the nutrient-deprived and hypoxic tumor microenvironment, ER stress reprograms glucose, lipid, and amino acid metabolism, exerting context-dependent effects that influence both tumor cell viability and immune regulation. Concurrently, ER stress remodels the metabolic fitness and functional states of immune cells, influencing T cell exhaustion, macrophage polarization, and dendritic cell maturation. Emerging evidence indicates that tumor- and immune-cell-derived metabolites (e.g., lactate, fatty acids, and tryptophan derivatives) exert both metabolic and immunomodulatory functions, thereby shaping a dynamic “ER stress–metabolism–immunity” axis that underlies cancer heterogeneity, immune evasion, and therapeutic resistance. In this review, we synthesize recent advances delineating how canonical ER stress pathways intersect with immunometabolic reprogramming across tumor and immune compartments, and we discuss how this integrated axis reshapes the tumor immune microenvironment (TIME). Targeting this integrated axis may unveil new strategies to overcome metabolic vulnerabilities and enhance the efficacy of immunotherapy.